Activation of p53 signaling and regression of breast and prostate carcinoma cells by spirooxindole-benzimidazole small molecules - Barakat, Assem; Alshahrani, Saeed; Al-Majid, Abdullah Mohammed; Alamary, Abdullah Saleh; Haukka, Matti; Abu-Serie, Marwa M.; Dömling, Alexander; Domingo, Luis R.; Elshaier, Yaseen A. M. M. (Frontiers in Pharmacology, 2024)
This study discusses the synthesis and use of a new library of spirooxindole-benzimidazole compounds as inhibitors of the signal transducer and activator of p53, a protein involved in regulating cell growth and cancer prevention. The text includes the scientific details of the [3+2] cycloaddition (32CA) reaction between azomethine ylide (AY) 7a and ethylene 3a within the framework of Molecular Electron Density Theory (MEDT). The mechanism of the 32CA reaction proceeds through a two-stage, one-step process, with emphasis on the highly asynchronous transition -state structure. The anti-cancer properties of the synthesized compounds, particularly 6a and 6d, were evaluated. The inhibitory effects of these compounds on the growth of tumor cells (MDA-MB 231 and PC-3) were quantified using IC50 values. This study highlights activation of the p53 pathway by compounds 6a and 6d, leading to upregulation of p21 p53 expression and downregulation of cyclin D and NF-κkB in treated cells.Additionally, we explored the binding affinity of spirooxindole analogs, particularly compound 6d, to MDM2, a protein involved in regulation of p53. The binding mode and position of compound 6d were compared with those of a co-crystallized standard ligand, suggesting its potential as a lead compound for further preclinical research.